Empowering Communities Based on Local Wisdom by Transforming Seashell Waste into Valuable Art: Pemberdayaan Masyarakat Berbasis Kearifan Lokal dengan Mengubah Limbah Kerang menjadi Karya Seni Bernilai - Effendi, Harris; Nurhaida, Dida; Busnetty, Ida; Octaviani, Dian; Sumiyarti, Sumiyarti; Iskandar, Layla Nurina Kartika (Universitas Lancang Kuning, 2024)
This community service activity was conducted in Sidamukti Village, Pandeglang Regency, Banten Province. Known for its coastal area, Sidamukti Village is home to a predominantly fishing community. The fishermen harvest various seafood, including clams, a type of seashell commonly used for its edible meat. While the fish is sold and the clam meat is consumed, the shells are often discarded as non-biodegradable waste that pollutes the environment. To address this issue, the PKM team from Universitas Trisakti explored an alternative approach by transforming seashell waste into valuable art. These activities employed the ABCD (Asset-Based Community Development) method, involving four key steps: 1) Observation; 2) Planning; 3) Implementation; and 4) Evaluation. The outcomes included the creation of handcrafted items such as necklaces, brooches, curtains, and lamps. As a result, the village community, particularly women, has become more empowered, and potentially generating additional income to support their families and enhance the local economy.